Analisis Pola Asuh Psikososial Pada Gizi Balita Pesisir di Kota Tarakan - Selvia Febrianti; Sheril Atikah; Slivia Kartikasari (HB PRESS, 2026)
Parenting goes beyond providing food; it involves psychosocial stimulation, which is crucial for a child's cognitive, physical, motor, and socio-emotional development. Parents often face various challenges during this process. In coastal areas, issues such as poor sanitation, limited food availability, and socio-economic factors can hinder the fulfillment of a toddler's nutritional needs, ultimately impacting their nutritional status. This study aims to determine the relationship between psychosocial parenting patterns and the nutritional status of toddlers in coastal areas. This is an analytical study using a cross-sectional approach. The subjects included parents of 200 toddlers aged 1–5 years, selected through proportional random sampling over a three-month period. Parenting styles were measured using the Parenting Style and Dimension Questionnaire (PSDQ), while children's nutritional status was determined using data from Maternal and Child Health (MCH) books. Data analysis was performed using the Chi-Square test at a 95% confidence level. The results indicated a significant relationship between psychosocial parenting patterns and the nutritional status of toddlers in coastal areas (p = 0.035). Parenting patterns play a vital role in determining nutritional status, as they encompass how parents meet the nutritional, health, and emotional needs essential for a child's optimal growth and development.